Farmers Participatory Site Specific Nutrient Management in Tidal Flooded Soil for High Yielding Aus Rice (Bangladesh Rice Journal, 2014)
Experiments were conducted in farmers fields at Bakergonj, Barisal and Kathaltoli, Potuakhali districts to develop site-specific nutrient management package for high yielding aus rice. The participating farmers delineated soil fertility as the most fertile (grade I), medium fertile (grade II) and the least fertile (grade III) soil. Omissions of N, P, and K were compared with added NPK fertilizers in different fertility grades. At Bakergonj, the NPK treat plots yielded 4.29, 4.36 and 2.09 t ha1 in soil grade I, II and III, respectively. Omission of N, P and K reduced grain yield by 0.76, 0.95 and 0.29 t ha-1 in grade I, 1.53, 0.87 and 1.25 t ha-1 in grade II and 0.64, 0 and 0.28 t ha-1 in grade III, respectively. At Kathaltoli, the grain yield (6.21 t ha1) in grade I was higher than grade II (5.58 t ha1) and grade III (5.11 t ha1). Omission of N, P and K reduced grain yield by 0.93, 0.18 and 0.09 t ha-1 in grade I, 1.30, 0.37 and 0.93 t ha-1 in grade II and 1.86, 1.30 and 1.30 t ha-1 in grade III, respectively. For Bakergonj, the calculated optimum doses of N were 34, 69 and 29 kg ha1, P were 4.0, 4.0 and 0.0 kg ha-1 and K were 7.0, 31.0 and 7.0 kg ha1 for fertility grade I, II and III, respectively. For Kathaltoli, the calculated optimum doses of N were 42, 59 and 84 kg ha1, P were 1.0, 2.0 and 5.0 kg ha-1 and K were 2.0, 23.0 and 33.0 kg ha1 for fertility grade I, II and III, respectively. The application of predicted fertilizer dose might increase rice yield in all fertility grades of soil in both the locations.DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20838Bangladesh Rice j. 2013, 17(1&2): 1-6